1996
DOI: 10.1093/nar/24.12.2404
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Family of TRF (DNA Topoisomerase I-Related Function) Genes Required for Proper Nuclear Segregation

Abstract: We recently reported the identification of a gene, TRF4 (for DNA topoisomerase related function), in a screen for mutations that are synthetically lethal with mutations in DNA topoisomerase I (top1). Here we describe the isolation of a second member of the TRF4 gene family, TRF5. Overexpression of TRF5 complements the inviability of top1 trf4 double mutants. The predicted Trf5 protein is 55% identical and 72% similar to Trf4p. As with Trf4p, a region of Trf5p is homologous to the catalytically dispensable N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
2
67
0
Order By: Relevance
“…Pap2 is not essential for this process in the cases we examined, most probably because it is partially redundant with Trf5, a TRAMP subunit homologous to and synthetically lethal with Pap2 (25,26). Further analysis of CUTs during meiosis revealed their staggered accumulation similar to SUTs and MUTs in sporulating MATa/α but typically not in starving MATα/α cells (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Pap2 is not essential for this process in the cases we examined, most probably because it is partially redundant with Trf5, a TRAMP subunit homologous to and synthetically lethal with Pap2 (25,26). Further analysis of CUTs during meiosis revealed their staggered accumulation similar to SUTs and MUTs in sporulating MATa/α but typically not in starving MATα/α cells (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Plasmid pCB427 (TRF4 URA3 CEN) was kindly provided by M. F. Christman (7). Plasmids for overexpression of cid1 and cid14 under the control of the GAL1 promoter were constructed by PCR amplification of the cid1 ϩ and cid14 ϩ open reading frames from S. pombe genomic DNA using the primer pairs CGCGGATCCGCGAATATGAACATTTCTTCT GCAC and ATAGTTTAGCGGCCGCATTCTTATTCACTCAGAATTGTCAC CATC and CGCGGATCCGCGGAGATGGGTAAAAAAAGCGTGTC and AT AGTTTAGCGGCCGCATTCTTATCTAAAAACGTTTGCGTATTTTTTTCGC, respectively, followed by digestion with BamHI and NotI and subsequent ligation into BamHI-and NotI-cleaved pYES2 (Invitrogen), generating pYES2cid1 and pYES2cid14.…”
Section: Methodsmentioning
confidence: 99%
“…Limited restriction mapping placed the remaining library clones into three classes, and a member of each class was sequenced. One class of suppressor carried inserts containing the TRF4-related gene, TRF5 (15). This demonstrates that at least two genes from the evolutionarily conserved TRF4 gene family affect cellular sensitivity to camptothecin.…”
Section: Suppression Of Camptothecin Hypersensitivity In the Trf4 Mutmentioning
confidence: 97%
“…We have discovered that TOP1 functions, together with a novel gene called TRF4 (for Topoisomerase Related Function), in the process of mitotic chromosome condensation (14,15). Furthermore, we have shown that the Trf4 protein is physically associated with Smc1p and Smc2p (14), proteins that bind directly to chromosomes and cause condensation (16).…”
mentioning
confidence: 99%